Disease reciprocity between gingivitis and obesity. (6th August 2020) - Goodson, J. Max
Abstract: Background: Many diseases seem to affect each other. This is particularly true of periodontal diseases that relate to many systemic diseases. For this reason, this study investigated the relationship between obesity and gingivitis in children by focusing on plasma and salivary metabolomic biochemicals. Methods: Whole saliva and plasma samples were taken from each of sixty‐eight 11‐year‐old children afflicted by different degrees of both gingivitis and obesity. Gingivitis was evaluated as the percent of sites considered erythematous. Obesity was determined by waist circumference. Untargeted metabolomic analysis defined 29 biochemicals significantly correlated between saliva and plasma, which included the collagen breakdown amino acid hydroxyproline (Hyp). Two‐sided t ‐tests and regression analysis were performed to compare these data from children with obesity alone, gingivitis alone, both, and neither. Results: Obese children exhibited signs of increased collagen turnover by being taller (14.4 cm) and having more permanent teeth (5.7). Analysis indicated a significant impact of obesity on gingivitis. Children with both diseases had 41.02% of gingival sites red whereas children with only obesity had 5.2% and children with only gingivitis had 19.16%. Hyp was increased in saliva by the combined presence of both diseases. The effects of gingivitis on obesity were in the same direction but generally not statistically significant. Conclusion: Obesity clearly augments gingivitis. Data suggest that interaction between gingivitis and obesity may exhibit disease reciprocity in which activated neutrophils are mutually shared to create collagen destruction and Hyp release into both saliva and plasma.